BAMBOO AS A STRUCTURE AND CONSTRUCTION MATERIAL IN THE DESIGN OF THE BAMBOO BUKIT VILLA - Nurazka, Azmi Afifah; Pynkyawati, Theresia; Davis, Muhammad Andre Mahardika Umarella; Garnida, Reva Regina (Journal of Architectural Research and Education, 2021)
Abstract - Bamboo is a building material that is easily renewed, light weight and has the strength and flexibility with a resistance of 3 to 4 years, therefore bamboo can be an alternative material for building materials. Just as in the Villa Bukit Saung Bambu, is a building located in Caringin Tilu, Bandung Regency, to have a high humidity and bermaterial bamboo in the whole building, down to its structure and construction. Apart from being an aesthetic, even this material makes a special attraction for visitors, as well as the raised foundation to make a stilt-style building, the joint system between  the horse- horse truss  structure  on the column, beams stacked in columns, column support on the foundation, floor construction that rests on the beams and roof coverings. The method used in this research is a qualitative descriptive method by means of direct observation in the field, observe the roof structure, columns, beams and foundations which are then compared with theories related to structure and construction, So it can be seen that bamboo can be an alternative building material, especially the structure of trusses horse- horse, beams, columns, floor and roof construction. Keywords: Villa Design, Structure and Construction, Bamboo Material